Comparative Analysis of the Reproduction of Style in Ukrainian, Russian, and Polish Translations of “Tom Sawyer” and “Huckleberry Finn” - Aloshyna, Maryna (Respectus Philologicus, 2014)
The author has studied the problems of the reproduction of stylistics in translation. Examples of domestication in translation have been analysed on the basis of different Ukrainian translations of The Adventures of Tom Sawyer and The Adventures of Huckleberry Finn, two famous novels written by Mark Twain. The first Ukrainian translators of Mark Twain’s novels in the first decade of the 20th century were Maria Zahirnia and Nastia Hrinchenko, wife and daughter of the prominent Ukrainian writer, scholar, and public activist Borys Hrinchenko. Their work was greatly influenced by the circumstances of the time (i.e., printing any translations into Ukrainian was banned in the Russian empire till 1905, no official body for the codification of the Ukrainian language existed, etc.). Later Ukrainian translations of the novel (Mytrofanov, Steshenko), together with Russian and Polish (by Chukovskii, Daruzes, Bilinski, and Tarnovski) were selected for comparative analysis with a consideration for their historical background. The linguistic and stylistic peculiarities of these translations have been studied. It is demonstrated that Zagirnya and Hrinchenko translations reproduce the original work quite exactly. Their translations have features of domestication and colloquialism, but at the same time, all important elements are fully reproduced. Their translations have a natural conversational tonality which corresponds to the original text. The later Ukrainian, Russian, and Polish translations under examination tend to keep to the norms of literary language to a greater extent. The level of domestication in these translations is lower (or even zero). Sometimes they include too-literary elements together with inadequate colloquial ones. Nevertheless, stylistically colored elements are successfully reproduced in these translations.
Keywords: style; history; recreation; translation; literary norm; tone; reproduction; diminution; domestication; phraseology